2013
DOI: 10.1177/2158244013515689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hypertension in Adansi South, Ghana

Abstract: Hypertension continues to emerge globally as one of the most dangerous cardiovascular disease risk factors. The toll of hypertension as a chronic disease on population health and the resultant impact on the often already stressed medical systems of developing nations is a serious concern. Shifting existing paradigm and resources from communicable to chronic disease prevention continues to be a formidable task. This article presents the results of a cross-section analysis of Adansi South, Ghana, residents (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Where systolic and diastolic hypertension were separately provided, we selected the higher of the two for analysis. In one study in which adolescents were included with the adult sample [ 26 ], hypertension in adolescents was defined as having SBP or DBP greater than or equal to the 95 th percentile in line with the recommendations of the National High Blood Pressure Education Program Working Group on High Blood Pressure in Children and Adolescents [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Where systolic and diastolic hypertension were separately provided, we selected the higher of the two for analysis. In one study in which adolescents were included with the adult sample [ 26 ], hypertension in adolescents was defined as having SBP or DBP greater than or equal to the 95 th percentile in line with the recommendations of the National High Blood Pressure Education Program Working Group on High Blood Pressure in Children and Adolescents [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…hypertension [7]). For all categorical variables, data are presented as percentage with 95% confidence interval (CI) as a measure of accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Given an α-level of 0.05, this study had a statistical power of 70% to detect a disease occurrence of 20% ± 7% (e.g. hypertension [ 7 ]). For all categorical variables, data are presented as percentage with 95% confidence interval (CI) as a measure of accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, increase in awareness, treatment and control rates of hypertension will have a huge and significant impact on Cardio Vascular Diseases (CVD) in Africa [27] . Elevated body mass index (BMI) has been identified as the main risk factor of HPT [28] . A recent study in Ghana found that over a third of the study population was either overweight or obese [22] .…”
Section: Introductionmentioning
confidence: 99%